Current challenges of organizational learning and cloud adoption technology toward SMEs’ performance - Ruslaini, Ruslaini; Supratikno, Hendrawan; Hariandja, Evo S. (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the effect of cloud computing on the business performance of Small and Medium Enterprises (SMEs) in Indonesia post-adoption and highlights the mediating role of organizational learning. Based on the Technology–Organization–Environment (TOE) framework, the study investigates the relationship between internal and external drivers of cloud adoption and the subsequent impact of cloud adoption on the learning processes and business performance at organizations. The research uses a hypothesized model framework to develop a quantitative study using CB-SEM with survey data from 315 SMEs using cloud computing as an ICT for more than a year. This means high management support and competitive pressure are potential motivators, whereas external support, regulatory support, and technology readiness do not significantly influence the adoption of the cloud. Results reveal the positive effect of cloud adoption on both organizational learning and firm performance. Additionally, organizational learning only partially mediates the relationship between cloud computing adoption and performance, thereby indicating the role of internal knowledge processes in converting technological investments into performance. These results show that the effectiveness of the cloud is magnified in the presence of learning at the organizational level. The study provides important insights for practitioners and policymakers seeking to enhance digitization efforts in the SME context.